Use of Tactile Contact Accompanying Health Promotion Messages During Routine Health & Physical Examinations: A Technique for Improving Compliance - Jay Johnson, Ralph (Journal of Public Health International, 2022)
A daunting challenge for health providers and medical practitioners is communicating the vital importance of health promotion and medical treatment adherence and compliance. This article is an evidence-based, best-practices commentary advocating the use of touch-accompanied verbal suggestions during the touching portions of routine, near-universal Health & Physical examinations. Notional case examples are presented; based on the professional literature, underlying Behavioral Mechanics are discussed. Touch-accompanied verbal health promotion messages skillfully deployed in routine Health & Physical examinations offer a non-harmful and efficient technique to synergistically and substantially enhance the probability of patient compliance with health improvement and medical treatment regimens. Though it is not a magic panacea, the public health applications, extensions and benefits are incalculable in terms of healthy behavior adoption. Additionally, if deftly conducted in accordance with best practices, it has the potential to greatly improve practitioner-patient relations and increase patient satisfaction. Further avenues of research inquiry are considered.
Keywords: Tactile contact; touching; program compliance; anchoring; treatment compliance; health improvement; health promotion